2022
DOI: 10.23917/dayasaing.v23i2.16180
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Kebijakan Pemberlakuan PPKM Pada Masa Pandemi Covid 19 Terhadap Industri Skala Kecil Dan Menengah Makanan Dan Minuman

Abstract: Penelitian ini bertujuan menganalisis pengaruh pandemic covid – 19 dan adanya pemberlakuan PPKM terhadap industry skala kecil dan menengah di Yogyakarta dengan mengambil studi kasus UMKM kaki lima yang terletak di kawasan Indomaret Jakal KM 12,5 Sleman, Yogyakarta. Penelitian ini menggunakan metode analisa deskriptif dengan pendekatan penulisan kualitatif. Sumber data pada penelitian ini berupa sumber data primer dan sumber data sekunder. Sumber data primer diperoleh dengan melakukan wawancara terhadap para pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…According to the 2020 World Bank report, the global economy contracted by 5.2%. This also means that SMEs have become victims of the outbreak and have caused a long-term decline in business conditions (Safitri & Dewa, 2022). The Covid-19 pandemic has also had a major impact on MSMEs in affected areas.…”
Section: Msmes During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the 2020 World Bank report, the global economy contracted by 5.2%. This also means that SMEs have become victims of the outbreak and have caused a long-term decline in business conditions (Safitri & Dewa, 2022). The Covid-19 pandemic has also had a major impact on MSMEs in affected areas.…”
Section: Msmes During the Covid-19 Pandemicmentioning
confidence: 99%
“…As a result of the Covid-19 pandemic, MSME owners, especially those in Riau Regency, have felt a huge impact (Ramadhan, 2020). Restrictions on community movement (PPKM) imposed by the government have had a negative impact on business continuity, such as not allowing residents to gather, closing roads that hamper the distribution of raw materials and consumer demand, as well as determining opening and closing times (Safitri & Dewa, 2022). The Covid-19 pandemic has become a complex challenge for all MSME owners, or even went bankrupt because they couldn't afford it.…”
Section: Msmes During the Covid-19 Pandemicmentioning
confidence: 99%
“…West Nusa Tenggara is one of the provinces in Indonesia affected by covid-19. Data released (Gremas NTB Date 9 September 2020) showed that 2,460 (15.86%) were treated, 2,269 (78.24%) recovered, and 171 (5.90%) died (Fajriani, 2022;Safitri & Dewa, 2022). From the data exposure, it can be concluded that covid-19 is still endemic in NTB.…”
Section: Introductionmentioning
confidence: 98%
“…The implementation of the Implementation of Emergency Community Activity Restrictions (PPKM) was first implemented on July 3, 2021-July 20, 2021, as an effort by the government to reduce the spread of COVID-19 in the Java-Bali region (Safitri & Dewa, 2022) According to data from the 2021 Bank Indonesia Annual Meeting report, the country's ecommerce transactions are projected to reach IDR 403 trillion in 2021. This amount grew 51.6% from the previous year which was IDR 266 trillion and is projected to be 530 trillion in 2022.…”
Section: Introductionmentioning
confidence: 99%